Tai-Chi Exercise Training and its Promising Therapeutic Impacts Among Older Community Dwelling Adults with Painful Knee Osteoarthritis - Ray, Marks (Journal of Aging Research And Healthcare, 2024)
Knee joint osteoarthritis, a chronic condition resulting in considerable disability, particularly in later life, not only impacts life quality significantly and severely, but is also strongly associated with the persistence of intractable pain, depression, helplessness, and a high falls injury risk. This narrative overview synthesizes the knowledge base regarding painful knee osteoarthritis and what is known about Tai Chi exercise participation in the context of reducing knee joint disability and its associated risk of one or more injurious falls, as well as pain and depression. To this end, all relevant articles published in the English language on the topic were sought. While most reports rely on Eastern observations, rather than Western medicine studies, collectively, these data reveal that Tai Chi practiced widely in Asia for many centuries may have an enormous positive impact on reducing distress and increasing function and autonomy among older adults living in the community and diagnosed as having knee osteoarthritis. They specifically suggest the increasing numbers of older adults diagnosed as having knee osteoarthritis can safely practice selected Tai Chi exercises with the expectation that consistent applications will enhance mobility, reduce pain and depression, plus instability and possible injurious falls, while reducing fatigue, even if surgery is forthcoming.
Keywords: Aging; Disability; Exercise; Falls; Intervention; Knee Joint; Older Adults; Osteoarthritis; Pain; Tai Chi